Pengaruh Likuiditas dan Solvabilitas terhadap Profitabilitas dan Ukuran Perusahaan sebagai Variabel Moderating - Angel Talenta Marpaung; Sarida Sirait; Calen Calen (Politeknik Bisnis Indonesia, 2023)
In this study aims to determine the effect of liquidity and solvency on profitability and company size as a moderating variable. The research method is quantitative descriptive. The total population and sample are 30 food and beverage sub-sector companies listed on the Indonesia Stock Exchange in the period 2020-2022. The results showed that liquidity and solvency had a significant effect on profitability in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2020-2022. The size of the company can moderate the influence of liquidity and solvency on profitability in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2020-2022. Keywords: Liquidity, Solvency, Profitability, Company Size